MÉTODOS AMBIENTALMENTE AMIGÁVEIS PARA A IODAÇÃO REGIOSSELETIVA DA 3,7,3’,4’-TETRAMETOXI-QUERCETINA - Ingrid T. L. Ramos; Telma M. G. da Silva; Tania M. S. da Silva; Celso A. Camara (Química Nova)
Halogenated compounds are valuable substrates for the field of organic synthesis and more specifically as reagents for coupling reactions. Environmental friendly procedures for regioselective iodination is the aim of this study, using four different methods previously described in the literature, that embrace green chemistry concepts, to obtain the 6- and 8-iodo-isomers of 3,7,3’,4’-tetramethoxy-quercetin. As traditional column chromatography does not resolve the mixture of isomers, the regioselectivity for iodination was quantified by use of HPLC. The use of a protic polar solvent improves selectivity for formation of the 8-iodo- isomers (tipically, I2, LiOH, MeOH, 3 h, 54% yield), while the use of a polar aprotic solvent or in the absence of a solvent favors formation of the 6-iodo- isomer (typically, I2, K2CO3, without solvent, 5 min, 60% yield). Twenty-one reaction procedures were investigated, five of which selectively gave the 6,8-diiodo-derivative. To the best of our knowledge, selective methods for the synthesis of this compound have not been described in the literature. The best condition was the neat reaction with N-iodo-succinimide with 68% yield in just a few minutes. All product yields are after column chromatography using silica gel, and characterized by usual methods, including 1H-NMR, 13C-NMR, IR and MS-TOF.